The Demand for Currency Relative to the Total Money Supply - Cagan, Phillip (Journal of Political Economy, 1958)
The object of the National Bureau of Economic Research is to ascertain and to present to the public important economic facts and their interpretation in a scientific and impartial manner.The Board of Directors is charged with the responsibility of ensuring that the work of the National Bureau is carried on in strict conformity with this object.2.